The Implementation of Infection Prevention and Control at the Lubuklinggau City Community Health Center: An Observational Study - Purba, Jeannita Sri Agustini; Syakurah, Rizma Adlia (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Introduction: Implementation of Infection Prevention and Control (IPC) is one of the characteristics of the quality of Health Care Services. Health care facilities must do the surveillance, IPC education and training. This aims to describe the implementation of IPC at the Lubuklinggau City Community Health Center (CHC).Methods: Descriptive qualitative study with a participant observation approach used.Result: The results showed that the priority problem was the ineffectiveness of the IPC team in implementing the IPC at the Lubuklinggau City CHC.Discussion: The preparation stage consists of socialization of IPC technical guidelines at CHC, assistance in implementing management and organization, assistance in disseminating policies, guidelines, SOPs, IPC, and IPC indicators, IPC implementation and reporting at the Primary Healthcare Facilities level, and IPC education and information at the level of health cadres and community leaders in every Health Center. The stages of monitoring and supervision are starting from the planning, implementation, and reporting stages. Evaluation is carried out with indicators of success in the form of accuracy and completeness of the report. Reporting is done at the end of the activity. Internal constraints that may occur are constraints on organizational culture, human resources, and funds, while external constraints include regional characteristics, reinforcing factors, and changing/accelerating factors. From these possible obstacles, strategies are made to overcome them.Conclusion: In this study, in order to further increase the effectiveness of the implementation of IPC at the Lubuklinggau City CHC, it is necessary to carry out continuous upgrading of the competence of health workers and IPC data at CHC.